Too complex and time-consuming to fit in! Physicians' experiences of elderly patients and their participation in medical decision making: a grounded theory study. Issue 3 (31st May 2012) - Ekdahl, Anne Wissendorff; Hellström, Ingrid; Andersson, Lars; Friedrichsen, Maria
Abstract : Objective: To explore physicians' thoughts and considerations of participation in medical decision making by hospitalised elderly patients. Design: A qualitative study using focus group interviews with physicians interpreted with grounded theory and completed with a questionnaire. Setting and participants: The setting was three different hospitals in two counties in Sweden. Five focus groups were conducted with physicians (n=30) in medical departments, with experience of care of elderly patients. Results: Physicians expressed frustration at not being able to give good care to elderly patients with multimorbidity, including letting them participate in medical decision making. Two main categories were found: 'being challenged' by this patient group and 'being a small part of the healthcare production machine'. Both categories were explained by the core category 'lacking in time'. The reasons for the feeling of 'being challenged' were explained by the subcategories 'having a feeling of incompetence', 'having to take relatives into consideration' and 'having to take cognitive decline into account'. The reasons for the feeling of 'being a small part of the healthcare production machine' were explained by the subcategories 'at the mercy of routines' and 'inadequate remuneration system', both of which do not favour elderly patients with multimorbidity. Conclusions: Physicians find that elderly patients with multimorbidity lead to frustration by giving them a feeling of professional inadequacy, as they are unable to prioritise this common and rapidly growing patient group and enable them to participate in medical decision making. The reason for this feeling is explained by lack of time, competence, holistic view, appropriate routines and proper remuneration systems for treating these patients.